Preparation method of granular lithium ion adsorbent loaded with biochar and LDHs
By generating LiCl·2Al(OH)3·nH2O type LDHs in situ in the biochar pore, the poor lithium ion selectivity and environmental pollution in the lithium resource extraction technology in the salt lake brine is solved, and efficient and environmentally friendly lithium is achieved Ion adsorption effect reduces cost and environmental risks.
Patent Information
- Application Number
- CN202310125104.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-02-16
AI Technical Summary
The existing lithium resource extraction technology in salt lake brine has problems such as poor lithium ion selectivity, high cost, environmental pollution and poor adsorbent fluidity. In particular, powdered adsorbents have insufficient fluidity and water permeability in industrial applications, and the granulation process The use of organic polymer materials in it leads to increased environmental risks and costs.
Using biochar as a carrier, LiCl·2Al(OH)3·nH2O type LDHs are generated by pyrolysis and carboxylation, and lithium ion adsorbent is generated in situ in the biochar pores, avoiding the use of organic polymers and organic solvents. Integrated adsorbent synthesis and granulation are in one step, which improves the fluidity and stability of the adsorbent.
High selectivity, efficient adsorption and simple desorption of lithium ions are achieved, the preparation cost is reduced, environmental pollution is avoided, the fluidity and stability of lithium-ion adsorbents are improved, and the lithium-specific adsorption performance is fully utilized.
Smart Images

Figure CN116251565B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium adsorption in salt lake brine, and in particular to a method for preparing a granular lithium ion adsorbent of biochar loaded with LDHs. Background Art
[0002] Lithium batteries are currently the secondary batteries with the best comprehensive performance and the most promising development prospects. They are widely used in new energy vehicles, electronic products, energy storage, aerospace and other fields. As the core element of lithium batteries, the development of lithium resources is of strategic significance for optimizing and upgrading the energy structure and achieving the "dual carbon" goal. It is estimated that by 2025, China's annual demand for lithium carbonate will reach 600,000 tons. China is one of the regions with relatively rich lithium resources, but they are mainly found in salt lake brines, and there are few high-quality resources, which makes China's lithium carbonate products rely heavily on imports. Low lithium ion concentration, high magnesium-lithium ratio, and complex water quality characteristics are the characteristics of the occurrence of lithium resources in China's salt lake brines, and are also the technical bottlenecks for the development of China's lithium resources. The development of lithium extraction technology with high selectivity, high efficiency, and green and pollution-free process is the key and difficulty in the development and extraction of lithium resources in China's salt lake brines. The main extraction technologies of lithium in salt lake brines include chemical precipitation, solvent extraction, electrodialysis, membrane separation, ion exchange and adsorption. Among them, adsorption technology has simple process, good selectivity, high recovery rate and is green and environmentally friendly. It is currently the most promising green lithium extraction technology for salt lake brines.
[0003] The adsorbents used in the adsorption method mainly include manganese spinel ion sieve, titanium dioxide oxide ion sieve, doped ion sieve, LDHs aluminum salt molecular sieve, organic ion exchange resin, etc. Among them, organic ion exchange resin adsorbents rely on Coulomb force to adsorb ions according to charge differences. They have poor selectivity for lithium and high cost, and are rarely used in lithium extraction from salt lake brine. Manganese spinel ion sieves have high selectivity for lithium ions, but they need to be prepared under high temperature conditions, and the Jahn-Teller effect of spinel is prone to structural collapse. There are problems such as easy dissolution and poor cycle stability. Acid is required for desorption, which is easy to corrode equipment and cause environmental pollution, and the cost is high. Titanium dioxide oxide ion sieves have high selectivity for lithium, but their synthesis process has high temperature requirements and relatively harsh synthesis conditions. There are problems such as easy dissolution and poor cycle stability. Acid is required for desorption, which is easy to corrode equipment and cause environmental pollution, and the cost is high. Although manganese spinel ion sieves, titanium dioxide oxide ion sieves, and LDHs aluminum salt molecular sieves have high selectivity for lithium ions, these adsorbents have small particle sizes after preparation and synthesis, and are in powder form. The adsorbents have poor fluidity, poor water permeability, large dissolution loss, and difficulty in solid-liquid separation, which is not conducive to industrial operation. Therefore, in industrial production, the adsorbent needs to be granulated to improve its practicality in extracting lithium from salt lake brine.
[0004] The current granulation technology mainly uses organic polymers as the supporting skeleton to coat and fix the prepared powdered adsorbent to achieve the purpose of granulating the adsorbent. The molding of the adsorbent mainly uses organic polymer materials to coat and granulate the adsorbent powder. There are mainly the following problems: ① Organic polymer materials are required as the supporting skeleton, and organic solvents are required in the molding process, which is expensive and has the potential risk of polluting the environment; ② In the polymer molding process, the adsorbent (adsorption site) will inevitably be masked, resulting in a loss of the utilization efficiency of the adsorbent, and at the same time, it will cause the adsorption and analysis process to become difficult; ③ The difficulty and cost of harmless treatment of the adsorbent after it is scrapped are high. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar, and the adsorbent prepared by the method has the characteristics of fast adsorption speed, high selectivity, high adsorption capacity, simple desorption, strong stability, etc. The method uses biochar as a carrier, realizes the in-situ generation of LiCl·2Al(OH)3·nH2O type LDHs in the biochar pores, integrates the preparation and synthesis of the adsorbent with the granular molding of the adsorbent in the same step, avoids the use of organic polymers, organic solvents and other reagents in the granulation process, reduces the cost of adsorbent preparation, avoids the impact of reagent leakage on the environment during the preparation process, and has the characteristics of simple operation, cleanliness and environmental protection.
[0006] The technical solution adopted by the present invention is: a method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar, comprising the following steps:
[0007] S1: Select wood as biomass raw material, wash and remove impurities on the wood surface, dry the wood, and then crush the wood into wood particles with a particle size of 0.1 mm to 0.5 mm;
[0008] S2: Weigh wood particles and porogen in a mass ratio of 1:1 to 1:5, ball-mill and mix them evenly to form a mixed material;
[0009] S3: pyrolyzing the mixed material in S2 at a temperature range of 500°C to 750°C for 1 to 24 hours under a nitrogen atmosphere, and then cooling to room temperature to obtain raw biochar;
[0010] S4: the original biochar is mixed evenly with a nitric acid solution with a concentration of 2 to 12 mol / L at a solid-liquid ratio of 1:2 to 1:5 g / ml, stirred at room temperature for 1 to 12 hours to fully remove the ash in the biochar, and subjected to carboxyl modification. After the reaction is completed, the biochar is washed with water until the pH value does not change, and dried to obtain biochar with a rich surface carboxyl group;
[0011] S5: adding the surface carboxyl-rich biochar to a soluble aluminum salt solution with a concentration of 0.1-2 mol / L, the surface carboxyl-rich biochar and the soluble aluminum salt solution are prepared according to a solid-liquid ratio of 1:2-1:10 g / ml, stirring at 20°C-60°C for 1-12 hours, drying after solid-liquid separation, and repeating this step 1-3 times;
[0012] S6: adding the biochar with rich surface carboxyl groups obtained in step S5 after being impregnated with aluminum salt solution to a mixed solution of soluble lithium salt and sodium hydroxide, wherein the concentrations of soluble lithium salt and sodium hydroxide in the mixed solution are both 0.1-3 mol / L, and the molar ratio of soluble lithium salt and sodium hydroxide in the mixed solution is 1:2-1:8, and the biochar with rich surface carboxyl groups after being impregnated with aluminum salt solution and the mixed solution are prepared according to a solid-liquid ratio of 1:2-1:5 g / ml, stirred at 20°C-80°C for 1-12h, dried after solid-liquid separation, to obtain a lithium adsorbent loaded with LiCl·2Al(OH)3·nH2O type LDHs.
[0013] The wood selected in step S1 is one or more of paulownia, pine, willow, apple and peach.
[0014] In step S2, the porogen is one or more of sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, ammonium bicarbonate, and urea.
[0015] In step S4, when the pH value remains unchanged after washing with water, the pH value ranges from 6 to 8.
[0016] In step S4, the temperature range of drying after washing is 70-150°C.
[0017] In step S5, the soluble aluminum salt is one or more of aluminum chloride, polyaluminum chloride, and sodium aluminate.
[0018] In step S6, the soluble lithium salt is one or more of lithium chloride, lithium hydroxide, and lithium sulfate.
[0019] The lithium adsorbent prepared in step S6 is added to a mixed solution of soluble aluminum salt, soluble lithium salt and sodium hydroxide, wherein the molar ratio of aluminum, lithium and sodium elements in the mixed solution is 1:2:5 to 1:4:10, and the lithium adsorbent and the mixed solution are prepared according to a solid-liquid ratio of 1:2 to 1:5 g / ml. After standing for 30 minutes, the mixture is heated to 20° C. to 60° C., stirred for 1 to 2 hours, and dried at 80 to 120° C. after solid-liquid separation.
[0020] The granular lithium ion adsorbent prepared by the preparation method of the biochar-loaded LDHs granular lithium ion adsorbent has a saturated adsorption capacity of ≥6.02 mg / g in one "adsorption-desorption" cycle, and the time used to reach adsorption saturation is ≤6.94 h. Only pure water is used for desorption, the desorption time is ≤1.29 h, the resolution rate is greater than 97.89%, the lithium-magnesium separation factor is greater than 97.5, and the average adsorption capacity in 15 "adsorption-desorption" cycles is ≥5.85 mg / g.
[0021] In the present invention, LDHs are hydrotalcite-like intercalation materials, wherein layered double hydroxide (LDH) is a general term for hydrotalcite (HT) and hydrotalcite-like compounds (HTLCs), and a series of supramolecular materials assembled by intercalation of these compounds are called hydrotalcite-like intercalation materials (LDHs).
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention uses biochar as a carrier to achieve the in-situ generation of LiCl·2Al(OH)3·nH2O type LDHs in the pores of biochar. This process integrates adsorbent synthesis and adsorbent granulation in one step, greatly improving the fluidity and water permeability of powdered LiCl·2Al(OH)3·nH2O type LDHs lithium adsorbent and reducing the loss of the adsorbent.
[0024] 2. The present invention uses biochar as a carrier to prepare granular lithium adsorbents. Compared with other adsorbent granulation molding technologies in the same industry, it avoids the use of polymer skeleton materials and organic solvents, and at the same time avoids the potential risk of releasing polymer skeleton materials and organic solvents into the environment during the molding process.
[0025] 3. The present invention loads the LiCl·2Al(OH)3·nH2O type LDHs lithium adsorbent with lithium-specific adsorption performance on the pores and surface of biochar, avoiding the masking of lithium-specific adsorption active sites caused by other granulation technologies using polymer materials to coat the lithium adsorbent, giving full play to the adsorption performance of the lithium adsorbent, and at the same time reducing the amount of LDHs lithium adsorbent per unit lithium adsorption amount.
[0026] 4. The biomass of the present invention is cheap, easily available and environmentally friendly. While obtaining a high-performance lithium adsorbent, the method reduces the preparation cost of the granular lithium adsorbent, shortens the preparation process and avoids environmental pollution.
[0027] The following is a further description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the LiCl·2Al(OH)3·nH2O type LDHs lithium adsorbent in Example 2 of the present invention.
[0029] Figure 2 This is the XRD spectrum of the LiCl·2Al(OH)3·nH2O type LDHs lithium adsorbent in Example 2 of the present invention.
[0030] Figure 3 This is a dynamic test data diagram of the lithium adsorption performance of the granular lithium ion adsorbent prepared in Example 2 of the present invention in brine.
[0031] Figure 4 This is a dynamic test data diagram of the lithium adsorption performance of the granular lithium ion adsorbent prepared in Example 3 of the present invention in brine.
[0032] Figure 5 This is a dynamic test data diagram of the lithium adsorption performance of the granular lithium ion adsorbent prepared in Example 4 of the present invention in brine.
[0033] Figure 6 This is a dynamic test data diagram of the lithium adsorption performance of the granular lithium ion adsorbent prepared in Example 5 of the present invention in brine.
[0034] Figure 7 This is a dynamic test data diagram of the lithium adsorption performance of the granular lithium ion adsorbent prepared in Example 6 of the present invention in brine. DETAILED DESCRIPTION
[0035] Example 1
[0036] A method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar, comprising the following steps:
[0037] S1: Select wood as biomass raw material, wash and remove impurities on the wood surface, dry the wood, and then crush the wood into wood particles with a particle size of 0.1 mm to 0.5 mm;
[0038] S2: Weigh wood particles and porogen in a mass ratio of 1:1 to 1:5, ball-mill and mix them evenly to form a mixed material;
[0039] S3: pyrolyzing the mixed material in S2 at a temperature range of 500°C to 750°C for 1 to 24 hours under a nitrogen atmosphere, and then cooling to room temperature to obtain raw biochar;
[0040] S4: The original biochar is mixed with a nitric acid solution with a concentration of 2 to 12 mol / L at a solid-liquid ratio of 1:2 to 1:5 g / ml, stirred at room temperature for 1 to 12 hours, washed with water until the pH value no longer changes after the reaction, and dried to obtain biochar with a surface rich in carboxyl groups; the original biochar can achieve the following purposes after being treated with a nitric acid solution: ① the ash in the biochar can be removed, the inorganic elements in the biochar can be dissolved, and the influence of these inorganic elements on the subsequent adsorbent preparation can be avoided, and the specific surface area can be further increased; ② the surface of the biochar is rich in a large number of carboxyl groups, which is convenient for the subsequent preparation of the adsorbent;
[0041] S5: adding the surface carboxyl-rich biochar to a soluble aluminum salt solution with a concentration of 0.1-2 mol / L, the surface carboxyl-rich biochar and the soluble aluminum salt solution are prepared according to a solid-liquid ratio of 1:2-1:10 g / ml, stirring at 20°C-60°C for 1-12 hours, drying after solid-liquid separation, and repeating this step 1-3 times;
[0042] S6: adding the biochar with rich surface carboxyl groups obtained in step S5 after being impregnated with aluminum salt solution to a mixed solution of soluble lithium salt and sodium hydroxide, wherein the concentrations of soluble lithium salt and sodium hydroxide in the mixed solution are both 0.1-3 mol / L, and the molar ratio of soluble lithium salt and sodium hydroxide in the mixed solution is 1:2-1:8, and the biochar with rich surface carboxyl groups after being impregnated with aluminum salt solution and the mixed solution are prepared according to a solid-liquid ratio of 1:2-1:5 g / ml, stirred at 20°C-80°C for 1-12h, dried after solid-liquid separation, to obtain a lithium adsorbent loaded with LiCl·2Al(OH)3·nH2O type LDHs.
[0043] The present invention uses biochar as a carrier to achieve in-situ generation of LiCl·2Al(OH)3·nH2O type LDHs in the biochar pores. This process integrates adsorbent synthesis and adsorbent granulation in one step, shortens the preparation process, greatly improves the fluidity and water permeability of powdered LiCl·2Al(OH)3·nH2O type LDHs lithium adsorbent, reduces adsorbent loss, and loads LiCl·2Al(OH)3·nH2O type LDHs lithium adsorbent with lithium-specific adsorption performance on the biochar pores and surface, avoids the masking of lithium-specific adsorption active sites caused by other granulation technologies using polymer materials to coat lithium adsorbents, and gives full play to the adsorption performance of the lithium adsorbent. Biochar is cheap, easily available and green and environmentally friendly, reduces the preparation cost of granular lithium adsorbents, and avoids environmental pollution.
[0044] The wood selected in step S1 is one or more of paulownia, pine, willow, apple and peach.
[0045] In step S2, the porogen is one or more of sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, ammonium bicarbonate, and urea.
[0046] In step S4, when the pH value remains unchanged after washing with water, the pH value ranges from 6 to 8.
[0047] In step S4, the temperature range of drying after washing is 70-150°C.
[0048] In step S5, the soluble aluminum salt is one or more of aluminum chloride, polyaluminum chloride, and sodium aluminate.
[0049] In step S6, the soluble lithium salt is one or more of lithium chloride, lithium hydroxide, and lithium sulfate.
[0050] The lithium adsorbent prepared in step S6 is added to a mixed solution of soluble aluminum salt, soluble lithium salt and sodium hydroxide, wherein the molar ratio of aluminum, lithium and sodium elements in the mixed solution is 1:2:5 to 1:4:10, and the lithium adsorbent and the mixed solution are prepared according to a solid-liquid ratio of 1:2 to 1:5 g / ml. After standing for 30 minutes, the mixture is heated to 20° C. to 60° C., stirred for 1 to 2 hours, and dried at 80 to 120° C. after solid-liquid separation.
[0051] The present invention adds the obtained lithium adsorbent loaded with LiCl·2Al(OH)3·nH2O type LDHs into a mixed solution of soluble aluminum salt, soluble lithium salt and sodium hydroxide at a solid-liquid ratio of 1:2-1:5 g / ml, heats, stirs and dries, and can continue to grow on the basis of the skeleton of the layered lithium adsorption active substance LDHs generated in situ in the existing biochar pores, thereby enhancing the adsorption performance of the lithium adsorbent loaded with LiCl·2Al(OH)3·nH2O type LDHs.
[0052] The granular lithium ion adsorbent prepared by the preparation method of the biochar-loaded LDHs granular lithium ion adsorbent has a saturated adsorption capacity of ≥6.02 mg / g in one "adsorption-desorption" cycle, and the time used to reach adsorption saturation is ≤6.94 h. Only pure water is used for desorption, the desorption time is ≤1.29 h, the resolution rate is greater than 97.89%, the lithium-magnesium separation factor is greater than 97.5, and the average adsorption capacity in 15 "adsorption-desorption" cycles is ≥5.85 mg / g.
[0053] Example 2
[0054] This example adopts the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 1, and the specific process is as follows:
[0055] 1. Wash the tung wood to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with KHCO3 at a mass ratio of 1:3 and grind it for 20 minutes, pyrolyze the mixture at 550℃ for 4 hours under nitrogen atmosphere, and cool it to room temperature after the reaction.
[0056] 2. Take 60g of pyrolyzed biochar and add it to 250ml of 3mol / L nitric acid solution, stir at 150r / min for 8h, wash with water until the pH value does not change after the reaction, and dry at 120℃;
[0057] 3. Weigh 72.4g aluminum chloride hexahydrate and dissolve it in 300ml deionized water, add the dried biochar, stir at 50℃ for 6h, separate the solid and liquid, and dry, repeat twice;
[0058] 4. Weigh 13.6g of anhydrous lithium chloride and 77.0g of sodium hydroxide and dissolve them in 250ml of deionized water, add the biochar obtained in step 3, mix well and let stand for 20min, stir at 40℃ for 2h, filter and dry at 120℃ to obtain a granular lithium ion adsorbent loaded with LDHs by biochar, the scanning electron microscope image of which is as follows: Figure 1 As shown, the XRD pattern is Figure 2 The scanning electron microscope image shows that the layered lithium adsorption active material is generated in situ in the biochar pores; the XRD peak comparison shows that the layered lithium adsorption active material is LiCl·2Al(OH)3·nH2O type LDHs.
[0059] Example 3
[0060] This example adopts the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 1, and the specific process is as follows:
[0061] 1. Wash the peach wood to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with NaHCO3 at a mass ratio of 1:2 and grind it for 20 minutes, pyrolyze the mixture at 650°C for 2 hours under nitrogen atmosphere, and cool it to room temperature after the reaction is completed;
[0062] 2. Take 50g of pyrolyzed biochar and add it to 200ml of 3mol / L nitric acid solution, stir at 200r / min for 4h, wash with water until the pH value does not change after the reaction, and dry at 120℃;
[0063] 3. Weigh 60g of polyaluminium chloride and dissolve it in 450ml of deionized water, add the dried biochar, stir at 60℃ for 4h, separate the solid and liquid, and dry, repeat 3 times;
[0064] 4. Weigh 16.2 g of anhydrous lithium chloride, 3.2 g of lithium hydroxide and 103.2 g of sodium hydroxide and dissolve them in 300 ml of deionized water, add the biochar obtained in step 3, mix well and stir at 60 ° C for 1.5 h, filter and dry at 120 ° C to obtain a granular lithium ion adsorbent loaded with LDHs by biochar.
[0065] Example 4
[0066] This example adopts the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 1, and the specific process is as follows:
[0067] 1. Wash the mixture of tung wood, peach wood and pine wood to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with urea at a mass ratio of 1:3 and grind it for 10 minutes, pyrolyze the mixture at 450°C for 4 hours under nitrogen atmosphere, and cool it to room temperature after the reaction is completed;
[0068] 2. Take 65g of pyrolyzed biochar and add it to 300ml of 6mol / L nitric acid solution. Incubate at 150r / min for 8h. After the reaction, wash with water until the pH value does not change and dry at 120℃.
[0069] 3. Weigh 31.2g of polyaluminium chloride and dissolve it in 250ml of deionized water, add the dried biochar, stir at 45℃ for 8h, separate the solid and liquid, and dry, repeat 3 times;
[0070] 4. Weigh 8.5g of anhydrous lithium chloride and 56g of sodium hydroxide and dissolve them in 200ml of deionized water, add the biochar obtained in step 3, mix well, stir at 50°C for 2h, filter and dry at 120°C;
[0071] 5. Weigh 145.5g aluminum chloride hexahydrate and 10.2g anhydrous lithium chloride and dissolve them in 200ml deionized water. Weigh 62.6g sodium hydroxide and dissolve them in 200ml deionized water. Mix the two solutions and stir them evenly. Add the adsorbent obtained in step 4. After standing for 30min, heat to 45°C and stir for 1h. After solid-liquid separation, dry at 105°C to obtain a granular lithium ion adsorbent loaded with LDHs by biochar.
[0072] Example 5
[0073] This example adopts the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 1, and the specific process is as follows:
[0074] 1. Wash the willow and apple wood mixture to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with KHCO3 at a mass ratio of 1:3 and grind it for 15 minutes, pyrolyze the mixture at 600℃ for 3 hours under nitrogen atmosphere, and cool it to room temperature after the reaction is completed;
[0075] 2. Take 65g of pyrolyzed biochar and add it to 300ml of 8mol / L nitric acid solution, stir at 200r / min for 5h, wash with water until the pH value does not change after the reaction, and dry at 120℃;
[0076] 3. Weigh 35.2g of polyaluminium chloride and dissolve it in 300ml of deionized water, add the dried biochar, stir at 40℃ for 6h, separate the solid and liquid and dry, repeat 3 times;
[0077] 4. Weigh 1.27g of anhydrous lithium chloride and 9.6g of sodium hydroxide and dissolve them in 300ml of deionized water. The concentration of lithium chloride is 0.1mol / L. Add the biochar obtained in step 3, mix well, stir at 45°C for 2.5h, filter and dry at 120°C.
[0078] 5. Weigh 168.6g of aluminum chloride hexahydrate and 14.8g of anhydrous lithium chloride and dissolve them in 180ml of deionized water. Weigh 111.7g of sodium hydroxide and dissolve them in 180ml of deionized water. Mix the two solutions and stir them evenly. Add the adsorbent obtained in step 4, let it stand for 30min, then heat to 40°C, stir for 1h, and dry at 105°C after solid-liquid separation to obtain a granular lithium ion adsorbent loaded with LDHs by biochar.
[0079] Example 6
[0080] This example adopts the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 1, and the specific process is as follows:
[0081] 1. Wash the willow and apple wood mixture to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with KHCO3 at a mass ratio of 1:3 and grind it for 15 minutes, pyrolyze the mixture at 600℃ for 3 hours under nitrogen atmosphere, and cool it to room temperature after the reaction is completed;
[0082] 2. Take 65g of pyrolyzed biochar and add it to 300ml of 8mol / L nitric acid solution, stir at 200r / min for 5h, wash with water until the pH value does not change after the reaction, and dry at 120℃;
[0083] 3. Weigh 65.2g of polyaluminium chloride and dissolve it in 300ml of deionized water, add the dried biochar, stir at 40℃ for 6h, separate the solid and liquid and dry, repeat 3 times;
[0084] 4. Weigh 38.2g of anhydrous lithium chloride and 126.2g of sodium hydroxide and dissolve them in 300ml of deionized water. The concentration of lithium chloride is 3mol / L. Add the biochar obtained in step 3, mix well, stir at 45°C for 2.5h, filter and dry at 120°C.
[0085] 5. Weigh 168.6g of aluminum chloride hexahydrate and 14.8g of anhydrous lithium chloride and dissolve them in 180ml of deionized water. Weigh 111.7g of sodium hydroxide and dissolve them in 180ml of deionized water. Mix the two solutions and stir them evenly. Add the adsorbent obtained in step 4, let it stand for 30min, then heat to 40°C, stir for 1h, and dry at 105°C after solid-liquid separation to obtain a granular lithium ion adsorbent loaded with LDHs by biochar.
[0086] The adsorption performance of the granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6 was measured, and the measurement method was as follows:
[0087] 50 g of the granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6 were taken and loaded into the adsorption column to perform a dynamic test of lithium adsorption performance in brine. Before the test, pure water was used to completely elute the LiCl in the lithium adsorption active component LDHs. The main ion concentration in the brine is: c(Li + )=165mg / L,c(Na + )=5000mg / L,c(K + )=7500mg / L,c(Mg 2+ )=33156mg / L,c(Cl - )=126363mg / L, the magnesium-lithium ratio in the brine is about 201. The brine flow rate is set to 15±0.5ml / min, and the brine is pumped into the adsorption column. The instantaneous lithium ion concentration in the brine flowing out of the adsorption column outlet is measured by sampling every 5min. When the lithium ion concentration of the adsorption column outlet does not change with time, the adsorption is considered to be saturated.
[0088] The amount of lithium adsorption is obtained by formula (1), where q is the amount of lithium adsorption, mg / g; C0 is the initial concentration of lithium ions in brine, mg / L; C e is the lithium ion concentration in the effluent when the adsorption is saturated, mg / L; V is the volume of brine flowing through the adsorption column in one adsorption cycle, ml; M is the mass of the adsorbent filled in the adsorption column, g.
[0089]
[0090] After adsorption saturation, pure water is used for desorption, and the desorption flow rate is 20±0.5ml / min. Samples are taken every 5 minutes to measure the instantaneous lithium ion concentration in the water effluent from the adsorption column. When the lithium ion concentration in the water effluent from the adsorption column does not change with time, the desorption is considered to be complete.
[0091] The lithium desorption rate is obtained by formula (2), where η d is the lithium resolution rate, %; C i is the lithium ion concentration in the desorption solution of the ith sampling, mg / L; v is the sampling volume of each time, ml; q is the adsorption amount of this "adsorption-desorption" cycle, mg / g.
[0092]
[0093] The above steps constitute one "adsorption-desorption" cycle.
[0094] The volume of brine used to reach adsorption saturation, the time used to reach adsorption saturation, the adsorption amount, the volume of pure water used for desorption, the desorption time, and the desorption rate in one "adsorption-desorption" cycle are shown in Table 1. From the data in Table 1, it can be seen that the saturated adsorption amount of 50g of the biochar-loaded LDHs granular lithium ion adsorbent prepared in Examples 2 to 6 in one "adsorption-desorption" cycle is 6.02mg / g, 6.35mg / g, 8.05mg / g, 6.13mg / g and 8.29mg / g, respectively, the volume of brine used to reach adsorption saturation is 4560ml, 5195ml, 6245ml, 5257ml and 6180ml, respectively, and the time used to reach adsorption saturation is 5.07h, 5.77h, 6.94h, 5.84h and 6.87h, respectively, indicating that the adsorbent has a large adsorption capacity, a fast adsorption speed, a small amount of brine used to reach adsorption saturation, and a high adsorption efficiency. It can be seen from the data in Table 1 that after 50g of the granular lithium ion adsorbent loaded with LDHs by biochar prepared in Examples 2 to 6 reaches adsorption saturation, lithium can be desorbed using only pure water, avoiding the use of other chemical reagents. The volumes of pure water used for complete desorption within one "adsorption-desorption" cycle are 1021ml, 1056ml, 1423ml, 935ml and 1542ml, respectively, and the desorption times are 0.85h, 0.88h, 1.19h, 0.78h and 1.29h, respectively, indicating that the amount of pure water used during desorption of the adsorbent is small, the desorption speed is fast, and the desorption rate is greater than 97.89%, with an extremely high lithium adsorption recovery rate.
[0095] Table 1 Performance data of the granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6 in one "adsorption-desorption" cycle
[0096]
[0097] In order to detect the selectivity of lithium ion adsorption of the biochar-loaded LDHs granular lithium ion adsorbent prepared in Examples 2 to 6, the magnesium ion concentrations in the inlet and outlet water of the adsorption column were simultaneously measured in one "adsorption-desorption" cycle.
[0098] The distribution coefficients of the granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6 for lithium ions and magnesium ions are obtained by formula (3), where K d is the distribution coefficient of the adsorbent for a certain ion, ml / g, K d The higher the value, the more preferentially the adsorbent adsorbs the ion; C0 is the initial concentration of a certain ion in brine, mg / L; C e is the concentration of a certain ion in brine at adsorption equilibrium, mg / L; V is the volume of brine flowing through the adsorption column when adsorption equilibrium is reached, ml; M is the mass of the adsorbent filled in the adsorption column, g.
[0099]
[0100] The separation factor of the granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6 for lithium ion and magnesium ion adsorption is obtained by formula (4), where is the separation factor of the adsorbent for lithium ions and magnesium ions. The higher the separation factor, the higher the adsorbent's preference for lithium ions over magnesium ions. is the distribution coefficient of the adsorbent to lithium ions, is the partition coefficient of the adsorbent to magnesium ions.
[0101]
[0102] Under the experimental conditions, the distribution coefficients and separation factors of the granular lithium ion adsorbents loaded with LDHs by biochar prepared in Examples 2 to 6 for the adsorption of lithium ions and magnesium ions are shown in Table 2. From the data in Table 2, it can be seen that the distribution coefficients of the granular lithium ion adsorbents loaded with LDHs by biochar prepared in Examples 2 to 6 for the adsorption of lithium ions are are 60.81ml / g, 61.13ml / g, 80.06ml / g, 57.45ml / g and 84.65ml / g respectively, and the distribution coefficient for magnesium ion adsorption It is only 0.59ml / g~0.83ml / g, indicating that the adsorbent has a much higher priority in the adsorption of lithium ions than magnesium ions, and the separation factors are all around 100, indicating that the adsorbent has a high selectivity in the adsorption of lithium ions.
[0103] Table 2 Selective adsorption performance data of granular lithium ion adsorbents loaded with LDHs prepared in Examples 2 to 6 for lithium and magnesium
[0104]
[0105] In order to detect the operational stability of the granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6, 15 "adsorption-desorption" cycles of lithium adsorption performance dynamic tests were performed on them. The average adsorption amount is shown in Table 3. The adsorption stability test results are shown in Table 3. Figure 3 to Figure 7 As shown in Table 3 and Figure 3 to Figure 7 It can be seen that the granular lithium ion adsorbents loaded with LDHs by biochar prepared in Examples 2 to 6 have a relatively high average adsorption capacity, all greater than 5.85 mg / g, and the adsorption performance is stable within 15 "adsorption-desorption" cycles of the dynamic test of lithium adsorption performance, indicating that the carboxyl-rich biochar on the surface of the prepared adsorbent provides sufficient support and fixation for the adsorption active ingredient LiCl·2Al(OH)3·nH2O type LDHs, and while LDHs are uniformly and massively loaded in its pores and surface, LDHs will not be lost in large quantities as the number of adsorption times increases, and the adsorbent has strong stability.
[0106] Table 3 Average adsorption amount of granular lithium ion adsorbent loaded with LDHs prepared in Examples 2 to 6 during 15 "adsorption-desorption" cycles
[0107] Example No. Average adsorption amount in 15 "adsorption-desorption" cycles / mg / g Example 2 5.85 Example 3 6.12 Example 4 7.25 Example 5 5.93 Example 6 7.53
[0108] Comparative Example 1
[0109] Compared with the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 5, the addition amounts of anhydrous lithium chloride and sodium hydroxide in step 4 are adjusted to 0.64 g and 4.8 g, respectively, and the rest is the same as in Example 5. The specific implementation process is as follows:
[0110] 1. Wash the willow and apple wood mixture to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with KHCO3 at a mass ratio of 1:3 and grind it for 15 minutes, pyrolyze the mixture at 600℃ for 3 hours under nitrogen atmosphere, and cool it to room temperature after the reaction is completed;
[0111] 2. Take 65g of pyrolyzed biochar and add it to 300ml of 8mol / L nitric acid solution, stir at 200r / min for 5h, wash with water until the pH value does not change after the reaction, and dry at 120℃;
[0112] 3. Weigh 65.2g of polyaluminium chloride and dissolve it in 300ml of deionized water, add the dried biochar, stir at 40℃ for 6h, separate the solid and liquid and dry, repeat 3 times;
[0113] 4. Weigh 0.64g of anhydrous lithium chloride and 4.8g of sodium hydroxide and dissolve them in 300ml of deionized water. The concentration of lithium chloride is 0.05mol / L. Add the biochar obtained in step 3, mix well, stir at 45°C for 2.5h, filter and dry at 120°C.
[0114] 5. Weigh 168.6g of aluminum chloride hexahydrate and 14.8g of anhydrous lithium chloride and dissolve them in 180ml of deionized water. Weigh 111.7g of sodium hydroxide and dissolve them in 180ml of deionized water. Mix the two solutions and stir them evenly. Add the adsorbent obtained in step 4, let it stand for 30min, then heat to 40°C, stir for 1h, and dry at 105°C after solid-liquid separation to obtain a granular lithium ion adsorbent loaded with LDHs by biochar.
[0115] 50g of the granular lithium ion adsorbent loaded with LDHs by biochar prepared in comparative example 1 was loaded into the adsorption column, and the dynamic test of lithium adsorption performance in brine was carried out, and the same test conditions and calculation methods were used as in examples 2 to 6. The saturated adsorption amount in one "adsorption-desorption" cycle was only 3.17mg / g, the volume of brine used to reach adsorption saturation was 3985ml, the time used to reach adsorption saturation was 4.43h, the volume of pure water used for desorption was 653ml, the desorption time was 0.54h, the resolution was 85.37%, and the separation factor for lithium and magnesium ion adsorption was 2.37%. Compared with the data of Example 5, it can be seen that the adsorbent prepared under the preparation conditions described in Example 1 has the characteristics of fast adsorption speed, high adsorption capacity, simple desorption, high selectivity and strong stability.
[0116] Comparative Example 2
[0117] Compared with the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent described in Example 6, the addition amounts of anhydrous lithium chloride and sodium hydroxide in step 4 are adjusted to 50.9 g and 168.1 g, respectively, and the rest is the same as in Example 6. The specific implementation process is as follows:
[0118] 1. Wash the willow and apple wood mixture to remove surface impurities, dry it, crush it to a particle size of 0.1-0.5 mm, mix it with KHCO3 at a mass ratio of 1:3 and grind it for 15 minutes, pyrolyze the mixture at 600℃ for 3 hours under nitrogen atmosphere, and cool it to room temperature after the reaction is completed;
[0119] 2. Take 65g of pyrolyzed biochar and add it to 300ml of 8mol / L nitric acid solution, stir at 200r / min for 5h, wash with water until the pH value does not change after the reaction, and dry at 120℃;
[0120] 3. Weigh 65.2g of polyaluminium chloride and dissolve it in 300ml of deionized water, add the dried biochar, stir at 40℃ for 6h, separate the solid and liquid and dry, repeat 3 times;
[0121] 4. Weigh 50.9g of anhydrous lithium chloride and 168.1g of sodium hydroxide and dissolve them in 300ml of deionized water. The concentration of lithium chloride is 4mol / L. Add the biochar obtained in step 3, mix well, stir at 45°C for 2.5h, filter and dry at 120°C.
[0122] 5. Weigh 168.6g of aluminum chloride hexahydrate and 14.8g of anhydrous lithium chloride and dissolve them in 180ml of deionized water. Weigh 111.7g of sodium hydroxide and dissolve them in 180ml of deionized water. Mix the two solutions and stir them evenly. Add the adsorbent obtained in step 4, let it stand for 30min, then heat to 40°C, stir for 1h, and dry at 105°C after solid-liquid separation to obtain a granular lithium ion adsorbent loaded with LDHs by biochar.
[0123] 50g of the granular lithium ion adsorbent loaded with LDHs by biochar prepared in comparative example 1 was loaded into the adsorption column, and the dynamic test of lithium adsorption performance in brine was carried out, and the same test conditions and calculation methods were used as in examples 2 to 6. The saturated adsorption amount in one "adsorption-desorption" cycle was only 4.93mg / g, the volume of brine used to reach adsorption saturation was 6525ml, the time used to reach adsorption saturation was 7.25h, the volume of pure water used for desorption was 1620ml, the desorption time was 1.35h, the resolution was 90.62%, and the separation factor for lithium and magnesium ion adsorption was 2.38kcal / cm2. The adsorption capacity of the adsorbent was 45.13, and after the third "adsorption-desorption" operation, the adsorption amount decayed to less than 50% of the adsorption amount of the first "adsorption-desorption" cycle. Compared with the data of Example 6, it can be seen that the adsorbent prepared under the preparation conditions described in Example 1 has the characteristics of fast adsorption speed, high adsorption capacity, simple desorption, high selectivity and strong stability.
[0124] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs identical or similar to the present invention belong to the protection scope of the present invention. The reagents, raw materials or methods described in detail in the present invention are all prior art and will not be further described in the present invention.
Claims
1. A method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar, characterized in that: The following steps are involved: S1: Select wood as biomass raw material, clean and remove impurities on the wood surface and dry it, then crush the wood into wood particles with a particle size of 0.1 mm to 0.5 mm; S2: Weigh wood particles and porogen in a mass ratio of 1:1 to 1:5, ball-mill and mix evenly to form a mixed material; S3: Pyrolyze the mixed material in S2 at a temperature range of 500°C to 750°C for 1 to 24 h under a nitrogen atmosphere, and then cool it to room temperature to obtain raw biochar; S4: The original biochar was mixed with a nitric acid solution with a concentration of 2-12 mol / L at a solid-liquid ratio of 1:2-1:5 g / ml, stirred at room temperature for 1-12 h, washed with water until the pH value no longer changed after the reaction, and dried to obtain biochar rich in carboxyl groups on the surface; S5: adding the surface carboxyl-rich biochar to a soluble aluminum salt solution with a concentration of 0.1-2 mol / L, the surface carboxyl-rich biochar and the soluble aluminum salt solution are prepared according to a solid-liquid ratio of 1:2-1:10 g / ml, stirring at 20°C-60°C for 1-12 hours, drying after solid-liquid separation, and repeating this step 1-3 times, wherein the soluble aluminum salt is one or more of aluminum chloride, polyaluminum chloride, and sodium aluminate; S6: adding the biochar with rich carboxyl groups on its surface after being immersed in the aluminum salt solution obtained in step S5 to a mixed solution of soluble lithium salt and sodium hydroxide, wherein the soluble lithium salt is one or more of lithium chloride, lithium hydroxide, and lithium sulfate, and the concentration of the soluble lithium salt and sodium hydroxide in the mixed solution is 0.1-3 mol / L, the molar ratio of soluble lithium salt and sodium hydroxide in the mixed solution is 1:2-1:8, the biochar with rich carboxyl groups on the surface after impregnation with aluminum salt solution is prepared with the mixed solution according to a solid-liquid ratio of 1:2-1:5 g / ml, stirred at 20℃-80℃ for 1-12h, dried after solid-liquid separation, and obtained a lithium adsorbent loaded with LiCl·2Al(OH)3·nH2O type LDHs, the prepared lithium adsorbent is added to a mixed solution of soluble aluminum salt, soluble lithium salt and sodium hydroxide, the molar ratio of aluminum, lithium and sodium elements in the mixed solution is 1:2:5-1:4:10, the lithium adsorbent and the mixed solution are prepared according to a solid-liquid ratio of 1:2-1:5 g / ml, stood for 30min, heated to 20℃-60℃, stirred for 1-2h, and dried at 80-120℃ after solid-liquid separation.
2. The method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar according to claim 1, characterized in that: The wood selected in step S1 is one or more of paulownia, pine, willow, apple and peach.
3. The method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar according to claim 1, characterized in that: In step S2, the porogen is one or more of sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, ammonium bicarbonate, and urea.
4. The method for preparing a granular lithium ion adsorbent loaded with LDHs by biochar according to claim 1, characterized in that: In step S4, when the pH value remains unchanged after washing with water, the pH value ranges from 6 to 8.
5. The method for preparing a granular lithium ion adsorbent containing biochar loaded with LDHs according to claim 1, characterized in that: In step S4, the temperature range of drying after washing is 70-150°C.
6. The granular lithium ion adsorbent prepared by the preparation method of a biochar-loaded LDHs granular lithium ion adsorbent according to claim 1 has a saturated adsorption capacity of ≥6.02 mg / g in one "adsorption-desorption" cycle, a time taken to reach adsorption saturation of ≤6.94 h, only pure water is used for desorption, the desorption time is ≤1.29 h, the resolution is greater than 97.89%, the lithium-magnesium separation factor is greater than 97.5, and the average adsorption capacity in 15 "adsorption-desorption" cycles is ≥5.85 mg / g.
